Proteinuria and proximal tubular epithelial cells: correlation between immunofluorescence, histology, and degree of proteinuria - Chow, Maria Bernadette CY; Yildiz, Vedat; Biederman, Laura; Dasgupta, Alana; Satoskar, Anjali A.; Chow, Aaron; Nadasdy, Tibor; Brodsky, Sergey V. (Frontiers in Nephrology, 2024)
Proteins are filtered from the blood through the glomerular filtration barrier. Filtered proteins are reabsorbed by proximal tubular epithelial cells (PTECs), which have been shown to possess the ability to regulate protein reabsorption. Histologically, these reabsorbed proteins are seen as tubular protein reabsorption droplets (TPRDs). Experimental studies indicate that PTECs play an important role in regulating proteinuria but the correlations between TPRD and the degree of proteinuria in human kidney biopsies have not been investigated in detail. Consecutive native kidney biopsies with non-proliferative glomerular disease performed at the OSUWMC for a 1-year period were analyzed. Cases with acute glomerular diseases and inadequate biopsies were excluded. The staining intensity and the percentage of TPRDs, as well as other morphologic parameters, were assessed. A total of 109 kidney biopsies were included in the study. A reverse correlation was identified between the percentage of albumin TPRDs and proteinuria (p = 0.047). There were positive correlations between proteinuria and the staining intensity for IgG TPRDs (p = 0.05) and the degree of acute tubular necrosis (ATN) (p = 0.015). In patients with no ATN, positive correlations between proteinuria and albumin and IgG TPRDs were seen, whereas in patients with ATN, these correlations were lost. A positive correlation was seen between proteinuria and chronic kidney injury. A strong correlation was noted between the degree of proteinuria and podocyte foot process effacement. Our data indicate that PTECs regulate proteinuria by absorbing proteins from the urine filtrate. Therefore, based on the human renal biopsy material, our study confirms that well-functioning renal PTECs play an important role in the regulation of proteinuria.